A Randomized Controlled Trial to Manage Postoperative Ocular Pain after Pterygium Excision with Conjunctival Autograft Transplantation with a Single Application of 2% Sodium Hyaluronate - Winai Chaidaroon; Sirawit Isipradit; Phit Upaphong; Chutikarn Dejkriengkraikul (Pain Research and Management)
Purpose. To assess the effectiveness of a single application of 2% sodium hyaluronate (SH) in controlling pain after pterygium excision as compared with that of a control group. Methods. We performed a prospective randomized controlled trial in the patients who underwent pterygium excision. The outcome of topical application of 2.0% SH was measured using the visual analogue scale (VAS), in comparison with that observed in a control group (without SH). The area of ocular surface defects was assessed by ImageJ freeware. Analysis of pain scores and ocular surface defects were observed from both groups immediately after the operation, Day 0, and 3 subsequent days. Results. Thirty patients were randomly divided into control group and SH treatment group. The initial area of the ocular surface defect on Day 0 was approximately the same for both groups (p=0.242). The medians of pain score assessed by the VAS on Days 0, 1, and 2 were 5, 3, and 0 for the SH group and 6, 5, and 3 for the control group, respectively. The pain score was statistically significantly decreased in the SH group compared to the control group on Day 1 (p<0.001) and Day 2 (p<0.001). The pain level of both groups was nearly the same on Day 3 (p=0.141). The area of ocular surface defects was significantly different between two groups on Day 1 (p<0.001) and Day 2 (p<0.001). Postoperative complications were not observed. Conclusion. A single topical application of 2% SH in pterygium excision was effective in relieving pain in the early postoperative period without any adverse effects. This innovation may provide alternative pain control in pterygium surgery.